miR-142-5p promotes renal cell tumorigenesis by targeting TFAP2B - Zhu, Maoshu (Oncol Lett, 2020)
The transcription factor AP-2 β (TFAP2B) serves an important role in kidney development. MicroRNAs (miRNAs) regulate carcinogenic pathways and have gained increasing attention owing to their association with human clear cell renal cell carcinoma (ccRCC) tumorigenesis. However, whether miRNAs could affect renal cell tumorigenesis by regulating TFAP2B expression has not been identified. The aim of this study was to investigate the effects of miRNA on TFAP2B and its potential role in cell growth, invasion and migration. PCR, western blot and dual luciferase reporter assays were performed to analyze the effects of miR-142-5p on TFAP2B. Furthermore, MTT, flow cytometry, wound healing and Transwell migration assays were used to analyze the effect of miR-142-5p on cell proliferation and migration. The results demonstrated that miR-142-5p targeted TFAP2B and downregulated the expression of TFAP2B at the mRNA and protein levels, promoting cell proliferation and migration in two ccRCC cell lines, 786-O and A-498. This phenomenon supported the theory that miR-142-5p may function as an oncogene in ccRCC. The potential clinical significance of miR-142-5p as a biomarker and a therapeutic target provides rationale for further investigation into miR-142-5p-mediated molecular pathways and how these may be associated with ccRCC development.